2021
DOI: 10.1039/d1cp02710g
|View full text |Cite
|
Sign up to set email alerts
|

Polymer network formation mechanism of multifunctional poly(ethylene glycol)s in ionic liquid electrolyte with a lithium salt

Abstract: We report a controlled polymer network gel electrolyte based on a multifunctional poly(ethylene glycol) (PEG) prepolymer (herein, tetrafunctional PEGs (tetra-PEGs) and bisfunctional linear PEGs (linear-PEGs)) and an ionic liquid (IL)-based...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…This choice of network topology was motivated by our experimental work mentioned above, where the core gel was synthesized by free radical polymerization involving tetrafunctional cross-linkers [ N , N′ -methylenebis­(acrylamide)]. Our model network could also represent tetra-PEG gels, , which consist of symmetrical tetrahedron-like (four-arm) PEG networks with excellent physical properties that are attributed to a high homogeneity of the network. To study possible effects of elastic strain, we compare two cases: slabs of isotropic gels and slabs of anisotropic gels which were deformed with a ratio very close to 2:1 in the lateral direction.…”
Section: Introductionmentioning
confidence: 99%
“…This choice of network topology was motivated by our experimental work mentioned above, where the core gel was synthesized by free radical polymerization involving tetrafunctional cross-linkers [ N , N′ -methylenebis­(acrylamide)]. Our model network could also represent tetra-PEG gels, , which consist of symmetrical tetrahedron-like (four-arm) PEG networks with excellent physical properties that are attributed to a high homogeneity of the network. To study possible effects of elastic strain, we compare two cases: slabs of isotropic gels and slabs of anisotropic gels which were deformed with a ratio very close to 2:1 in the lateral direction.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, the polymer/ionic liquid system has been well studied because of the high ionic conductivity and nonvolatile properties of ionic liquids. 28,29 Nevertheless, the traditional solvent-casting method to build SPEs is usually energy-intensive and has poor reproducibility, making it difficult for large-scale processing. [28][29][30][31][32][33][34] Polymerizationinduced phase separation (PIPS) is another processing method for composites, with which the domain size and connectivity of different separated phases can be adjusted during the polymerization process.…”
Section: Introductionmentioning
confidence: 99%
“…28,29 Nevertheless, the traditional solvent-casting method to build SPEs is usually energy-intensive and has poor reproducibility, making it difficult for large-scale processing. [28][29][30][31][32][33][34] Polymerizationinduced phase separation (PIPS) is another processing method for composites, with which the domain size and connectivity of different separated phases can be adjusted during the polymerization process. 5,[35][36][37][38] The in situ processing using PIPS to construct SPEs for LIBs is usually carried out using the separator-assisted approach, 39 in which the polymerized precursor is injected into the preassembled battery with a separator for subsequent assembly and in-cell polymerization, 4,6 but the inactive separator limits the ion-conduction of SPEs and the monomer may be reactive with Li-metal for LMBs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[21][22][23] This TetraPEG gelation can be applied to various complex solutions, such as ionic liquid-and organic solvent-based electrolyte solutions containing Li salt, as well as aqueous solutions. [24][25][26][27][28] The resulting TetraPEG gels exhibit high mechanical strength even at low polymer concentrations (o5 wt%) and can be used to realize Li-ion battery gel electrolytes with a high ionic conductivity comparable to that of liquid electrolytes. [28][29][30][31] Recently, Tosa et al reported a solid polymer electrolyte based on a homogeneous TetraPEG network and Li salt, which they synthesized via a Michael addition reaction between TetraPEG-MA and TetraPEG-NH 2 prepolymers in organic electrolyte solutions at high temperature (333 K).…”
Section: Introductionmentioning
confidence: 99%